Wastewater from Olive Oil Production Environmental Impacts, Treatment and Valorisation - Souabi, Salah; Anouzla, Abdelkader (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book summarizes the recent research development concerning olive oil wastewater management: characterization, environmental impact, recovery and treatment. The book combines different chapters on the management of olive oil rejects using simple techniques with low investment and operating costs. The main focus of the book is: - Diagnosis, impacts of olive oil waste, and regulations - The valorization of the margins and the olive waste - Wastewater treatment and recovery - Evaluation of investments and operating costs of treatment techniques - Shaped by experience, the authors present their view and approach to each focus area of managing liquid and solid waste produced by crushing units.
Chapter 1: Valorization of olive tree by-products by co-composting -- Chapter 2: Olive oil mill wastewaters treatment methods -- Chapter 3: Olive mill wastewater: Treatment and valorization -- Chapter 4: Valuable materials from OMW -- Chapter 5: Study the value of olive mill wastewater and their impact on the receiving environment -- Chapter 6: A state-of-art review on the use of olive-oil mill wastewater for human purposes -- Chapter 7: Olive mill waste water bioactive molecules: applications in animal farming -- Chapter 8: Physicochemical characterization and estimation of the pollution degree of olive oil mill wastewaters from the cold extraction system and the traditional system -- Chapter 9: Characterization of top soils subjected to poorly controlled olive oil production wastewater and its effect on litter decomposition -- Chapter 10: Open ponds for effluent storage, a pertinent issue to olive mill wastewater (OMW) management in a circular economy context: Benefits and environmentalimpact -- Chapter 11: Olive mill wastewaters (OMWWs) a natural tank gorged with bioactive molecules -- Chapter 12: Management of olive oil mill wastewater in Morocco: Production, impacts, and treatment -- Chapter 13: Turkey's olive mill wastewater (OMWW) problems and some suggestions -- Chapter 14: Future trends in olive industry waste management: A literature review.
Keywords: Water; Hydrology; Pollution; Chemistry, Technical; Biology; Refuse and refuse disposal; Water; Pollution; Industrial Chemistry; Biological Sciences; Waste Management/Waste Technology